ANALISIS KINERJA KEUANGAN DENGAN RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS, DAN PROFITABILITAS PADA CV ORA ET LABORA PERIODE 2018-2021 - Widuri, Andi Fika; Ihwanudin, Nandang (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2023)
For companies, one way to find out their financial performance is by analyzing the ratio to their financial statements. CV Ora Et Labora is an example of a company that is able to develop and survive in carrying out the survival of the company. This company is the object of research used by the author in this study because it has complete financial statements and is in accordance with the various criteria that the author uses. This research was conducted using secondary data in the form of annual financial statements of CV Ora Et Labora for the 2018-2021 period and conducted a direct review of the company. Financial ratio analysis using liquidity, activity, profitability, and solvency ratios is then interpreted based on industry ratio standards. From the results of the calculation of the entire ratio, it was found that this company has excellent financial performance in terms of all measuring instruments.